LEGAL PROTECTION OF INVESTORS ON THE LAJNAH BISNIS SYARIAH (LBS) PLATFOREM - Lisnawati, Depi; Mujib, Abdul; Kusmastuti, Ines Prasheila (Universitas Muhammadiyah Surabaya, 2024)
Sharia investment through digital platforms in Indonesia. One of the Sharia investment platforms in the form of sukuk offerings is Lajnah Bisnis Syariah (LBS). The problem is that investments carried out at LBS experience many obstacles that are detrimental to investors. This is exacerbated by the absence of legal protection for investors in investor agreements with LBS. This research examines further the legal protection and regulations for LBS investors when facing problems with sukuk offerings that affect results and harm investors. The research method used is normative empirical. This qualitative data analysis method describes policies relating to legal protection for investors against risks associated with issuers experiencing problems with Sukuk. The findings of this research are that investors have the opportunity to understand better companies issuing sukuk, so they can reach better profit-sharing agreements and manage the risks associated with managing the business. The availability of information aims to reduce problems that may arise in sukuk offerings by issuers and increase capital market efficiency. This research concludes that PT Tri Buana Cemerlang investors offering sukuk through the Lajnah Bisnis Syariah (LBS) platform are protected by preventive legal mechanisms with problem resolution through non-litigation channels